Pemeliharaan Arsip Statis pada Kantor Arsip Dokumentasi dan Perpustakaan Kota Solok - Riza, Rizky Metra; Syahyuman, Syahyuman (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper aims to discuss: 1) supervision of the maintenance of archives in the Archives, Documentation, and Solok City Library, 2) the state of the equipment used in the maintenance of archives in the Archives, Documentation, and Solok City Library, 3) HR in the maintenance of the state archives in the Archives, Documentation, and City Library Solok. From the results of this discussion to the authors conclude, 1) archival surveillance activities in the Office of Archives, Library and Documentation Solok City supervised by archivists themselves. However, this activity is supposed to do this regularly as it should have done so visible damage to its archives. A lot of dust on the shelf archive, the archive folder also cover damaged, torn. Not least there are also records that dirty because it is often held by the hand of man, 2) equipment used in the maintenance of records in the Office of Archives, Documentation, and City Library Solok severely limited by the willingness of the means in the form of equipment and materials needed. So the activity is still done manually. Fire detector (Smock detecter) as well as a tool to measure temperature humidity (dehumidifien) no. In addition to material treatment suasah also obtained. Coupled with archive storage space does not meet the standard. Even places that are used for processing, sorting, and archival storage are in one room, 3) archives archivists who do not care and that too few people are assigned to other parts. Power archivists set in archival education only 5 people but the number of personnel there numbered 19 people. Of the five professional none in the maintenance of archives. For that archivists are not set in archival education at the Archives, Documentation, and City Library archives Solok provide technical guidance, so that employees can see or obtain knowledge about the archives. Includes seminars archivists in archives, training related to maintenance procedures archives. Even working with ANRI Jakarta in maintaining records in a way to bring the archive to be repaired there. Keywords: archives ; archivists themselves; maintaining records